2017
DOI: 10.12788/jhm.2815
|View full text |Cite
|
Sign up to set email alerts
|

The Weekend Effect in Hospitalized Patients: A Meta‐Analysis

Abstract: Hospital inpatients admitted during weekends may have a higher mortality rate compared with inpatients admitted during the weekdays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
100
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 66 publications
(83 reference statements)
4
100
1
2
Order By: Relevance
“…Recent studies suggest that differences in patient outcomes may be associated with weekend admission, a phenomenon termed “weekend effect.” A weekend effect has been reported in the United States and Europe for a variety of severe, emergent conditions requiring prompt diagnosis and intervention, such as peptic ulcer disease‐related gastrointestinal (GI) hemorrhage, GI cancers, myocardial infarction, and stroke . Meta‐analysis for all‐cause weekend versus weekday mortality with subgroup analysis by personnel staffing levels, procedure rates, times, and delays, and illness severity, has shown that patients admitted on the weekends have a consistently higher relative risk of mortality . Several predictors for poor outcomes related to weekend admissions have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that differences in patient outcomes may be associated with weekend admission, a phenomenon termed “weekend effect.” A weekend effect has been reported in the United States and Europe for a variety of severe, emergent conditions requiring prompt diagnosis and intervention, such as peptic ulcer disease‐related gastrointestinal (GI) hemorrhage, GI cancers, myocardial infarction, and stroke . Meta‐analysis for all‐cause weekend versus weekday mortality with subgroup analysis by personnel staffing levels, procedure rates, times, and delays, and illness severity, has shown that patients admitted on the weekends have a consistently higher relative risk of mortality . Several predictors for poor outcomes related to weekend admissions have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Meta-analysis for all-cause weekend versus weekday mortality with subgroup analysis by personnel staffing levels, procedure rates, times, and delays, and illness severity, has shown that patients admitted on the weekends have a consistently higher relative risk of mortality. 12 Several predictors for poor outcomes related to weekend admissions have been reported. Transfer status on the weekend for emergent cases like abdominal aortic aneurysm rupture may be associated with higher mortality than weekday transfers.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effect of this reduction in services upon acute care is well established, and a higher mortality has been reported for patients undergoing procedures on the weekend . Furthermore, the admission of a patient to hospital on the weekend has been associated with increased mortality when compared with admission during the week although it is unclear whether these differences in mortality persist after adjustment for weekend differences in patient comorbidities and illness severity …”
Section: Introductionmentioning
confidence: 99%
“…Sie fanden, unter Einbeziehung von 12 retrospektiven und einer prospektiven Studie, eine signifikant erhöhte Chance postoperativ zu versterben und eine erhöhte Gesamtmorbidität bei Nachtoperationen gegenüber operativen Eingriffen am Tage [1]. Weitere Übersichtsarbeiten und populationsbasierte Studien haben zumindest für Europa und Nordamerika außerdem eine erhöhte Mortalität bei Patienten gezeigt, die außerhalb der sogenannten Kernarbeitszeit stationär oder am Wochenende hospitalisiert wurden [2,3]. Zuletzt haben Chen et al (2019) eine Metaanalyse von 68 Studien, von denen zwei Drittel aus den USA und Großbritannien stammten und die sich auf Daten von ca.…”
unclassified